PROFITABILITY OF AGRICULTURAL COOPERATIVES. SELECTED METHODICAL ASPECTS OF MEASUREMENT AND ANALYSIS - Małgorzata Matyja (Journal of Agribusiness and Rural Development, 2018)
The analysis of profitability enables the assessment of business efficiency while also providing information on the company’s current economic situation and further development opportunities. The purpose of this paper is to identify the definitional and analytical problems related to the profitability of agricultural cooperatives, and to exemplify the possible solutions. The sample used in this study consists of ca. 100 agricultural production cooperatives based in Poland. Trend extrapolation and analysis of variance and correlation were the techniques employed to investigate the profitability (ROE, ROA, ROS, VI) and its relationship with main lines of production and the size (UAA) and quality (soil valuation index) of agricultural land. The results of research allowed to conclude that the profitability of agricultural cooperatives is decreasing each year; it does depend neither on the main line of production nor on the size and quality of agricultural land. The need for an in-depth study of profitability of agricultural cooperatives was pointed out. It was also stated that the potential determinants of profitability may include management quality and other internal and organizational issues.